1975
DOI: 10.1530/jrf.0.0420587
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Pattern of the Y-Bearing Human Spermatozoa in Density Gradient Centrifugation

Abstract: Numerous attempts have been made to separate the X-and Y-bearing spermatozoa of mammals (Kiddy & Hafs, 1971 12,000, 26,400, 49,600, 63,600 or 77,500 g. The centrifuged tubes were photographed by indirect illumination and the densitometer tracing was made from the photographic negative. The tubes were fractionated by aspiration of the different banding regions, using a special glass pipette with a finely drawn outlet. The fractions were washed with Ca2+-free Ringer and concentrated by centrifugation. The sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…The most effective way to influence sex ratios in offspring is to determine the sex before fertilization and therefore separate populations of X-and Y-chromosome bearing spermatozoa. Several techniques based on principals such as velocity (BEAL et al, 1984;BEERNINK and ERICSSON, 1982;DMOWSKI et al, 1979;ERICSSON et al, 1973;ZAVOS, 1985), density (BHATTACHARYA, 1958;BHATTACHARYA, 1962;BHATTACHARYA et al, 1966;FLAHERTY et al, 1997;KANEKO et al, 1983;KOBAYASHI et al, 2004;LOPEZ et al, 1993;PYRZAK, 1994;QUINLIVAN et al, 1982;ROHDE et al, 1975;ROSS et al, 1975;SCHILLING and THORMAEHLEN, 1977;SHASTRY et al, 1977;VIDAL et al, 1993;WANG et al, 1994b;WANG et al, 1994a), electric surface charge (BLOTTNER et al, 1994;ENGELMANN et al, 1988;MANGER et al, 1997;SEVINC, 1968;SHIRAI et al, 1974;SHISHITO et al, 1974;UWLAND and WILLEMS, 1975), and immunologically relevant structures (ALI et al, 1990;BENNETT and BOYSE, 1973;BLECHER et al, 1999;ERICKSON et al, 1981;HANCOCK, 1978;HENDRIKSEN et al, 1993;PINKEL et al, 1985;SILLS et al, 1998) have been developed and tested. None of these methods were able to produce statistically significant separa...…”
Section: Techniques To Identify Sex-related Characteristics Of Spermamentioning
confidence: 99%
“…The most effective way to influence sex ratios in offspring is to determine the sex before fertilization and therefore separate populations of X-and Y-chromosome bearing spermatozoa. Several techniques based on principals such as velocity (BEAL et al, 1984;BEERNINK and ERICSSON, 1982;DMOWSKI et al, 1979;ERICSSON et al, 1973;ZAVOS, 1985), density (BHATTACHARYA, 1958;BHATTACHARYA, 1962;BHATTACHARYA et al, 1966;FLAHERTY et al, 1997;KANEKO et al, 1983;KOBAYASHI et al, 2004;LOPEZ et al, 1993;PYRZAK, 1994;QUINLIVAN et al, 1982;ROHDE et al, 1975;ROSS et al, 1975;SCHILLING and THORMAEHLEN, 1977;SHASTRY et al, 1977;VIDAL et al, 1993;WANG et al, 1994b;WANG et al, 1994a), electric surface charge (BLOTTNER et al, 1994;ENGELMANN et al, 1988;MANGER et al, 1997;SEVINC, 1968;SHIRAI et al, 1974;SHISHITO et al, 1974;UWLAND and WILLEMS, 1975), and immunologically relevant structures (ALI et al, 1990;BENNETT and BOYSE, 1973;BLECHER et al, 1999;ERICKSON et al, 1981;HANCOCK, 1978;HENDRIKSEN et al, 1993;PINKEL et al, 1985;SILLS et al, 1998) have been developed and tested. None of these methods were able to produce statistically significant separa...…”
Section: Techniques To Identify Sex-related Characteristics Of Spermamentioning
confidence: 99%
“…Rohde et al (1975) described fractionation of human sperm on sucrose density gradients, and found increasing proportions of FO sperm as density increased. A controversial report by Shastry et al (1977) stated that F1 human sperm sedimented through a Percoll gradient more rapidly than FO sperm.…”
Section: Cell Density and Sedimentation Ratesmentioning
confidence: 99%
“…Numerous reports have been published in the past three decades in which the authors claim to have demonstrated the use of physical methods to separate X-bearing from Y-bearing sperm. [12][13][14][15][16][17][18][19] Some of these studies appear to be well designed; unfortunately, the claimed results generally cannot be reproduced. The interested reader should consult Meistrich 20 for a complete discussion of the potential and limitations of physical methods for separation of X and Y sperm.…”
Section: Physical Factorsmentioning
confidence: 99%